2015
DOI: 10.1017/s0033291715000793
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing and interaction skills training for parents of young adults with recent-onset schizophrenia and co-occurring cannabis use: 15-month follow-up

Abstract: The results support the sustained effectiveness of FMI in reducing cannabis use in patients with recent-onset schizophrenia at 15 months follow-up. Findings were not consistent with regard to the long-term superiority of FMI over RFS in reducing parents' distress and sense of burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…We may conclude that the training program led to meaningful changes in caregiver’s lives. Our results confirm the findings of an earlier study [ 12 ] where families who completed the IST reduced burden effectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We may conclude that the training program led to meaningful changes in caregiver’s lives. Our results confirm the findings of an earlier study [ 12 ] where families who completed the IST reduced burden effectively.…”
Section: Discussionsupporting
confidence: 91%
“…The psychosocial intervention in this therapy targeted the patient’s closest family member or relative. Smeerdijk and colleagues found that the combination of family motivational interventions (MI) and the IST was effective in reducing family members’ worrying and burden [ 12 ]. A systematic evaluation by Signe & Elmståhl [ 13 ] showed that 90% of family caregivers expressed great satisfaction with respect to psychosocial interventions intended to meet caregiver’s needs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a trial conducted in the Netherlands demonstrated that a family motivational intervention (parents n = 53, patients n = 37) which focuses on establishing a supportive family environment, compared to routine family support (parents n = 44, patients n = 38) was effective at reducing frequency and quantity of cannabis use in adolescent and young adult patients with schizophrenia at 3 month follow-up (Smeerdijk et al, 2012). This was sustained at 15-month follow-up (Smeerdijk et al, 2015). There were no significant changes from baseline in use of alcohol or any other drugs other than cannabis during this trial.…”
Section: Psychosismentioning
confidence: 95%
“…A Cochrane review published in 2014 concluded that there is a lack of good quality evidence for the efficacy of any psychosocial or pharmacological treatment at reducing cannabis use in psychosis (McLoughlin et al, 2014) (Table 3). Studies conducted since the publication of that review have had mixed findings (Rabin et al, 2018; Sheridan Rains et al, 2019; Smeerdijk et a., 2015). Tailored and time-intensive cannabis-focused treatment plans have not provided better outcomes than treatment as usual (Wisdom, Manuel, & Drake, 2011).…”
Section: Psychosismentioning
confidence: 99%
“…Consider reminding family members about the initial ground rules for counseling, that blaming or shaming is not allowed. Some studies have reported the benefits of teaching family members MI techniques such as asking open-ended questions, using reflections, and eliciting change talk (Smeerdijk et al, 2012(Smeerdijk et al, , 2015, although Miller and Rollnick (2013) cautioned against the use of MI by persons with emotional investment in the outcome.…”
Section: Evoking Motivation To Changementioning
confidence: 99%